2014
DOI: 10.1111/ped.12242
|View full text |Cite
|
Sign up to set email alerts
|

Effects of enuresis nocturna on parents of affected children: Case–control study

Abstract: The parents of children with EN seem to experience increased levels of anxiety. Their desire to continue the marital relationship, the overall quality of their marital relationship and their comfort as a family may also be negatively affected by having a child with EN.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
12
1
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 17 publications
1
12
1
1
Order By: Relevance
“…This underlines the need for medical personnel to ask parents about enuresis in their children. This view is further strengthened by the knowledge that enuresis, if left untreated may have both a short‐term and long‐term psychological impact on the child and the family .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This underlines the need for medical personnel to ask parents about enuresis in their children. This view is further strengthened by the knowledge that enuresis, if left untreated may have both a short‐term and long‐term psychological impact on the child and the family .…”
Section: Discussionmentioning
confidence: 99%
“…In one study of 243 children with enuresis in a south‐western region of Nigeria, only nine of the parents had spoken to a medical doctor about it . Although only a minority of parents with children with enuresis seek medical help, childhood enuresis is not entirely a benign condition and significant long‐term adverse psychological effects have been reported . Studies carried out about three decades ago documented that most parents had poor knowledge about the causes of enuresis and a significant proportion employed punishment as a means of treating enuresis .…”
Section: Introductionmentioning
confidence: 99%
“…14 From the perspective of the Dyadic Adjustment Scale (DAS), it was observed that the scores relating to affection were reduced in parents of children with nocturnal urinary incontinence. 30 The studies assessed indicated the parents' difficulty in coping with family agreement in basic situations, which promotes less empathy between the fathers and the mothers and makes the family management difficult. The relationship between peers was seen as a risk factor for monitoring, supervision, and involvement with the children.…”
Section: Changes That Impact On Daily Family Lifementioning
confidence: 99%
“…This factors are regarded as having an impact on family life and as contributors to the permanence of nocturnal urinary incontinence, because there is a large increase in household expenses due to the multiple clothes washing and constant changing of bed sheets and mattresses. 13,15,21,30 Urinary incontinence involves more than one physical disorder. It affects the family routine and can cause psychological disorders such as stress, anxiety, and depression in children and their caregivers.…”
Section: Changes That Impact On Daily Family Lifementioning
confidence: 99%
“…Increased appetite, weight gain and sedation are among the most common side effects of it, whereas, the incidence of risperidone-induced enuresis is under 1% (3,4). Not only the patient but also all family members may be negatively affected by enuresis nocturna (6). Not only the patient but also all family members may be negatively affected by enuresis nocturna (6).…”
mentioning
confidence: 99%